Risk Treatment - Grima, Simon; Torre-Enciso, María Isabel Martínez; Castelli, Maurizio (The FERMA-rimap series ;, 2025)
The need to manage risk is increasingly featured in legislation and regulations. Simultaneously, the need to integrate risk management into the general management practices of organisations is fast becoming a key objective for all stakeholders. In addition, the drive to improve corporate governance is compelling organisations to examine the manner in which they manage risks and operational and strategic levels. The second volume of The FERMA-rimap Series explores examples of organisational risk and the aims and benefits of an effective risk management strategy. All risk professionals have a duty to remain updated with the evolution of the risk landscape. The FERMA-rimap Series serves as a proactive, continuous and dynamic learning and research platform to respond to risk managers' present and future educational and professional needs. The volumes set a crucial standard taxonomy for European Risk Professionals and an essential reading for students aspiring to gain a qualification in Risk Management.